Omega-3 Fatty Acid Fortification of Flax Through Nutri-Priming - Marques, Edward; Darby, Heather; Kraft, Jana (Frontiers in Nutrition, 2021)
Omega-3 (n-3) fatty acids (FA) play an essential role in human physiology and health. As a result, a variety of n-3 FA-fortified functional foods have become commercially available for human consumption. These fortified functional foods are created through various processes; however, nutri-priming, a potentially promising fortification approach, has not been utilized to develop plant-based n-3 fortified foods. We sought to determine whether nutri-priming is a viable option to enrich seeds and sprouts with n-3 FA. Additionally, we assessed whether n-3 FA nutri-priming would inhibit germination of the primed seeds. To address these goals, we nutri-primed brown flax in three priming solutions, control [0% fish oil (FO)], 10% FO and a 20% FO solution, and determined the FA content and profile of seeds and sprouts and germination percentage of primed seeds. n-3 FA nutri-priming with FO altered the FA profile in seeds and sprouts, with increases in the absolute content of 20:5 n-3, 22:6 n-3, 22:5 n3, 18:4 n-3, and 20:4 n-6. However, n-3 FA nutri-priming did not increase the absolute content of 18:2 n-6, 18:3 n-3, total saturated FA, total monounsaturated FA, total polyunsaturated FA, total n-6 FA, or total n-3 FA. Our results also showed that n-3 nutri-priming decreased the germination percentage of primed seeds, with 10 and 20% FO priming solution reducing germination by 4.3 and 6.2%, respectively. Collectively, n-3 nutri-priming modified the n-3 FA profile in flax; however, the process does not increase the total n-3 FA content and inhibits germination of primed seeds. Further research utilizing different seed types, oil types, and oil concentrations needs to be conducted to fully determine if n-3 nutri-priming is a commercially viable approach for n-3 fortification of seeds and sprouts.